Effect of potential risk factors on renal functions in simultaneous bilateral total knee arthroplasty - Akar, Bedrettin; Ugur, Fatih; Yucel, Mucahid Osman; Aytug, Ferhan (Frontiers in Surgery, 2024)
ObjectiveThis retrospective study investigated the risk factors leading to a decrease in Renal glomerular filtration rate (eGFR) and the development of acute kidney injury (AKI) during the early postoperative period in patients undergoing simultaneous bilateral total knee arthroplasty (SBTKA).MethodsSBTKA was performed on 862 patients between 2014 and 2021 in a single center, by a single surgeon. The risk factors affecting the development of AKI were analyzed by monitoring the changes in pre-and postoperative serum creatinine (Scr) levels and eGFR values. RIFLE criteria were used to evaluate the kidney functions of the patients, who were followed up for an average of 6 months.ResultsWhile there was no decrease in eGFR or AKI in 818 patients postoperatively, eGFR decreased and AKI of different stages developed in 44 patients, according to the RIFLE criteria. Of the 44 patients with AKI, 31 had Risk, 9 had Injury, 3 had Failure, and one had Loss of kidney function. Two patients with American Society of Anaesthesiologists (ASA) class IV died due to deepening of postoperative renal dysfunction.ConclusionWe found that the direct risk factors in SBTKA in terms of eGFR decrease and AKI development include long operation time, increased need for blood transfusion, and diabetic nephropathy, while increased body mass index (BMI) is an indirect risk factor. When planning for a SBTKA, we presume that a thorough analysis of these factors will decrease AKI risk.